2020
DOI: 10.11591/ijece.v10i4.pp4155-4161
|View full text |Cite
|
Sign up to set email alerts
|

The students’ acceptance of learning management systems in Saudi Arabian Universities

Abstract: For distance learners, continuous official education is very important for improving knowledge and learning experience in order to meet the career challenges in the modern world. This work studies the success factors which affect the use of LMS and evaluates the ability to apply the proposed model in the field of distance learning (DL) particularly in higher education. The survey was carried out on higher education learners who were included in the DL instructions. This work has utilized a questionnaire that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…And this indicated that technical support has a positive influence on the acceptance of the technology, and this corresponds with research conducted by Alsmadi (2020), Chatti andHadoussa (2021), Al-Mamary et al, (2021), and Badwelan and Bahaddad (2021). Students face technical problems and are unable to solve them.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…And this indicated that technical support has a positive influence on the acceptance of the technology, and this corresponds with research conducted by Alsmadi (2020), Chatti andHadoussa (2021), Al-Mamary et al, (2021), and Badwelan and Bahaddad (2021). Students face technical problems and are unable to solve them.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the results proved that content quality has a positive influence on the acceptance of the technology, and this corresponds with research conducted by Almaiah et al (2022), Alsmadi (2020), andBinyamin et al (2019). Hence, H4 is accepted.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Most respondents agreed that the online platform is easy to use and favoured the tools and features available through the online platform. User satisfaction and behavioral intent to use directly influence net gain on system usage [27]. Respondents agreed that online platforms allow them to teach at a convenient time zone and area.…”
Section: Discussionmentioning
confidence: 99%
“…Expectation-confirmation theory model will be used for user acceptance test (UAT). User acceptance is used to evaluate the system's success factors, which are unclear and low acceptance [20], [21]. This application can be used on the prepared prototype and the target user was find randomly.…”
Section: User Acceptance Testmentioning
confidence: 99%